Characterization of amylase and protease activity in the digestive tract of two teleosts (Labeo rohita and Anabas testudineus) with diﬀerent feeding habits - Debnath, Sanjeet; Saikia, Surjya Kumar (Acta Biologica Szegediensis, 2021)
Two teleosts (Rohu, Labeo rohita and Koi, Anabas testudineus), both with contrasting feeding habits (herbivorous versus carnivorous) were studied for amylase and protease activity concerning different regions of their digestive tracts. Significant differences in enzymatic activity across different regions of the digestive tracts were observed. Rohu, with three equal regions of the stomachless gut, showed the highest amylolytic activity at the posterior digestive tract but the highest proteolytic activity is limited to mid region. Contrary to such observation, Koi with three distinct regions of the digestive tract (stomach, pyloric caeca and intestine), the pyloric caeca exhibited the highest specific activity for both amylase and total protease. The optimum pH and temperature conditions were determined concerning the activity for both amylase and protease.